PENGARUH NILAI EKONOMI PEKERJAAN IBU RUMAH TANGGA TERHADAP KESEJAHTERAAN KELUARGA SUBYEKTIF - Puspitawati, Herien (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2009)
The analysis of the economic value of wives’ household productions is less likely to be paid attention. The aims of this study were to measure the economic value of wives’ household productions and the factors that affected the economic value of household productions and family subjective quality of life. The study was conducted at Hambaro Village, Sub-District of Nanggung, Bogor that was chosen purposively, in April to August 2008, by using cross sectional study design. The samples were 110 housewives. Results showed that the average of economic value of household productions done by housewives was around Rp 6.223,00 daily. It was found that most of families were categorized as poor families both from an income approach and from an expenditure approach. The results also showed that mothers tend to allocate their time longer for her female than male child under five years old (for caring and parenting), thus, the economic value of household productions for parenting domestic activities was higher for female than male child. Moreover, the economic value was lower with the increased of child age, however, the value was higher with the higher the numbers of child under five years old. The results also showed that there were positive effects of numbers of family members, the length of husband’s education, wife’s age, the child’s age, expenditure/capita/month and the economic value of household productions for maintaining home activities toward the family subjective quality of life. Lastly, there was a negative effect of husband’s age towards the family subjective quality of life.